Educational needs of children with migration experience in terms of language development at their early childhood stage. Theoretical assumptions and state of research - Katarzyna Stankiewicz; Anna Żurek (Problemy Wczesnej Edukacji)
This article discusses the educational needs of pupils with migration experience, in terms of their language development, considering both the language of the host country and the parents’ native language. The introductory character of the considerations is based on a critical analysis of selected literature on the subject. The analysis of theoretical assumptions and empirical research on the needs and support for the language development of early school‑age pupils reveals different needs of children depending on the type of their migration experience. In addition to specific educational needs, general needs essential for academic success are also emphasized, regardless of the migration type. The conclusion underlines the importance of individualizing the educational process to support the linguistic development of children with migration experience.